ROMAN BAYANGAN MEMUDAR: KEHIDUPAN SEBUAH KELUARGA INDO KARYA E. BRETON DE NIJS KAJIAN POSKOLONIAL - Insum Malawat (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
This study about aspect of narrative structure, enviroment languages aspect, aspect and body or racial which contains in novel “Bayangan Memudar: Kehidupan Sebuah Keluarga Indo by E. Breton de Nijs “. Theory is used in this study is post colonial theory that load  the culture of Europe colonial that ever abode in  Indonesia. The purpose of this study  is give visible image of eurasian family life in literary works. Result of this study is found narrative structure, enviroment languages aspect that mention Hindia’s location, this aspect include which extend and narrow scope. Narrating viewpoint is single first person. Besides, it is found sense racial aspect.